The Existence of the Development of Islamic Education Management in Madrasas: Actualization of Principles and Values of Hadith Perspectives in the Contemporary Era - Hamdi, Hamdi; Hartati, Zainap; Mualimin, Mualimin; Tajudinnur, Tajudinnur (UIR Press, 2024)
This research aims to describe the existence of developments in Islamic education management in madrasas and the actualization of the principles and values ​​of the hadith perspective in the contemporary era. The type of research used is mixed method, with the informants for this research being teachers and students. Data collection techniques use descriptive, observation and interviews, and are analyzed by reducing data, presenting data and making conclusions. The results of this research show that planning, organizing, implementing and supervising MTs Hidayatul Muhajirin Palangka Raya has been running effectively, with high motivation to advance the school, integration of Islamic education management values ​​and the Hadith of the Prophet, establishing Islamic brotherhood and institutional cooperation. Understand the principles of Islamic education management, which support decision making and curriculum planning. In addition, regular evaluations are carried out to ensure the implementation of Hadith principles in school management. This research has implications for education in good madrasa management in accordance with Islamic guidance in the future